Comunidades de aves frugívoras e nectarívoras e disponibilidade de recursos em dois estádios sucessionais de regeneração de Mata Atlântica - Silva, Bruna Gonçalves da (2012)
The availability of food resources in different degrees of regeneration of a forest may contribute to possible variations in species abundance and composition of bird communities. The main objective of this study is to investigate the relationship between the structure of frugivores and nectarivores bird communities and the availability of food resources - flowers and fruit - in two successional stages of regeneration (initial-secondary and advanced) of the Atlantic Forest. To reach this goal, frugivores and nectarivores birds were monitored in representative sites of these stages, considering seasonality and production of flowers and fruits at each stage over a year. The frugivores and nectarivores were compared in richness, species composition, relative abundance and diversity. We used fixed point counts for sampling birds, and to estimate the production of flowers and fruits, we delimited three replicates of four plots (10x10m) at each stage of succession. The two studied successional stages differed significantly in most of the analyzed vegetation structure variables. The composition and relative abundance of some bird species also showed differences between the two stages of regeneration, but not quantitative parameters as richness and diversity. There were variations in plant community phenological curves and in the amount of the floral production between the two successional stages. The relative abundance of frugivores had a significantly positive relationship with the amount of available ripe fruits. In the advanced stages, the relative abundance of nectarivores birds had a significantly positive relationship to the number of individuals of flowering epiphytic plant species; while in secondary stages of regeneration there was no change in the abundance of nectarivores birds in response to floral resource availability. Thus, in areas that are not continuous to primary forests may occur in a declining population of frugivorous and nectarivorous birds in response to variations in the phenological curves and food shortages causing changes in the processes of breeding and selection of plant species, which can bring significant implications for the conservation of birds and plants.